Validation of flavivirus infectious clones carrying fluorescent markers for antiviral drug screening and replication studies - Cherkashchenko, Liubov; Gros, Nathalie; Trausch, Alice; Neyret, Aymeric; Hénaut, Mathilde; Dubois, Gregor; Villeneuve, Matthieu; Chable-Bessia, Christine; Lyonnais, Sébastien; Merits, Andres; Muriaux, Delphine (Frontiers in Microbiology, 2023)
Flaviviruses have emerged as major arthropod-transmitted pathogens and represent an increasing public health problem worldwide. High-throughput screening can be facilitated by the use of viruses that express easily detectable marker proteins. Developing molecular tools such as reporter-carrying versions of flaviviruses for studying viral replication and screening of antiviral compounds therefore represents a top priority. However, the engineering of flaviviruses carrying either fluorescent or luminescent reporters remains challenging due to the genetic instability caused by marker insertion; therefore, new approaches to overcome these limitations are needed. Here, we describe reverse genetic methods which includes design and validation of infectious clones of Zika, Kunjin and Dengue viruses harboring different reporter genes for infection, rescue, imaging and morphology using superresolution microscopy. It was observed that for different flaviviruses constructs with identical design displayed strikingly different genetic stability while corresponding virions resembled wild-type virus particles in shape and size. A successful strategy was assessed to increase stability of rescued reporter virus and permit antiviral drug screening based on quantitative automated fluorescence microscopy and replication studies.